2008
DOI: 10.1161/hypertensionaha.108.112003
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypercoagulability

Abstract: Abstract-Orthostatic stress causes significant plasma shift and raises transmural pressure in lower extremities, resulting in an increase in endothelial activation and plasma proteins concentrations, possibly including coagulation factors. This may lead to activation of the coagulation system during standing. To test this hypothesis, we recruited 18 healthy volunteers (9 females and 9 males; mean age: 25Ϯ1.2 years; body mass index: 21.7Ϯ0.5 kg/m 2 ). Hemodynamics, plasma shift (extrapolated from sequential hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 44 publications
6
28
0
Order By: Relevance
“…However, it is unclear if markers of coagulation system activation respond similarly during these protocols. Reductions in central blood volume by LBNP (38) or orthostatic stress (10,21,36) activate the coagulation cascade; therefore, it is likely that central hypovolemia during BL elicits comparable changes in coagulation when the degree of central hypovolemia is similar between LBNP and BL.…”
Section: Our Study Provides Noteworthy Data That Directly Compare Blomentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unclear if markers of coagulation system activation respond similarly during these protocols. Reductions in central blood volume by LBNP (38) or orthostatic stress (10,21,36) activate the coagulation cascade; therefore, it is likely that central hypovolemia during BL elicits comparable changes in coagulation when the degree of central hypovolemia is similar between LBNP and BL.…”
Section: Our Study Provides Noteworthy Data That Directly Compare Blomentioning
confidence: 99%
“…The suction applied during LBNP produces a pressure gradient that pulls fluid from the intravascular compartment to the extravascular space in the lower body, resulting in hemoconcentration (5,29,34). Plasma protein concentration and blood viscosity both increase, which creates a procoagulant milieu due to increased interactions between coagulation factors and cellular contributors to coagulation (12,17,21). However, BL has the opposite effect.…”
Section: Our Study Provides Noteworthy Data That Directly Compare Blomentioning
confidence: 99%
“…89,90 Hypertension increases shear stress leading to activation of NFκB and Egr-1, and subsequently to upregulation of TF gene expression. 91,92 Angiotensin-convertingenzyem (ACE) inhibitors downregulate TF expression in vivo, 93 while angiotensin II upregulates it in vascular cells via the angiotensin II type 1 receptor.…”
Section: Hypertensionmentioning
confidence: 99%
“…In 2008, Masoud and colleagues described a novel physiological mechanism, 'orthostatic procoagulation,' in which endothelial-dependent procoagulant and anticoagulant systems are activated during prolonged static standing [18].…”
mentioning
confidence: 99%
“…Significant increases in concentration or activity of blood coagulation factors in response to orthostatic stress have been reported [16][17][18]. Cvirn and colleagues reported that the procoagulant effect of orthostatic stress persists for up to 20 min after presyncope, which is the endpoint of cardiovascular stress.…”
mentioning
confidence: 99%